Nonfatal and fatal cardiovascular disease events in CPAP compliant obstructive sleep apnea patients - Myllylä M.; Hammais A.; Stepanov M.; Anttalainen U.; Saaresranta T.; Laitinen T. (Springer Verlag, 2022)
Purpose: Obstructive sleep apnea (OSA) is suggested to predispose to cardiovascular disease (CVD) events. It is uncertain whether compliance to continuous positive airway pressure (CPAP) treatment could attenuate the risk. We explored this issue in long-term CPAP users and untreated controls.
Methods: Retrospective observational cohort of CPAP-treated and control patients were pairwise matched for gender, age, and apnea–hypopnea index (AHI). The study end point was a composite of nonfatal and fatal CVD events. Cox regression model was used to determine the association between CPAP treatment and event-free survival.
Results: A total of 2060 patients (75.8% male, mean age 56.0 ± 10.5 years), of which 76.4% had moderate–severe OSA, were included. In the CPAP-treated group (N = 1030), the median use of CPAP was 6.4 h/day during a median follow-up of 8.7 years. The control group (N = 1030) was followed for a median of 6.2 years after the CPAP treatment had ended. The study end point occurred in 14.4% (N = 148) of the CPAP-treated and in 18.8% (N = 194) of the control patients (p = 0.006). Using the Cox regression model adjusted for gender, age, AHI, body mass index, and history of CVD, hypertension, type 2 diabetes, and chronic obstructive pulmonary disease at baseline, a beneficial association between CPAP treatment and CVD risk was observed (hazard ratio 0.64, confidence interval 95% 0.5–0.8, p < 0.001).
Conclusions: CPAP treatment was associated with a decreased risk of nonfatal and fatal CVD events. Majority of the patients were compliant to CPAP. The association was demonstrated independent from common cardiovascular risk factors and AHI.